Demonstrating in the internet age: a test of Castells' theory. (3rd March 2020) - Slavina, Anna; Brym, Robert
ABSTRACT: Some social movements researchers argue that the Internet globalises protest and equalises cross-national inequalities in opportunities for activism. Critics warn against such techno-optimism, highlighting continued individual-level inequalities and country-level variation in protest participation. In this paper, we operationalise Manuel Castells' theory of social movement development to test the extent to which contemporary demonstrators share the characteristics of global activists. We also examine how country-level economic and political institutions affect levels of protest and moderate the relationship between individual-level predictors and activism. We find support for Castells' contention that use of online media is a significant predictor of protest. However, we also find that having a sense of global connectedness does not significantly affect one's likelihood of engaging in demonstrations. Protest participation continues to be stratified by traditional markers of social privilege including education and gender. Moreover, national political and economic contexts have independent effects on protest and moderate how individual-level political and economic grievances affect civic engagement.